TRUCK CRANE HOIST BOOM BUCKLING RELIABILITY ANALYSIS BASED ON PROBABILISTIC AND NON-PROBABILISTIC HYBRID MODEL AND BAYESIAN NETWORK - QU FuZheng; SUN Qi; XIE ZhengYi (Jixie qiangdu)
The accidents of truck crane happen frequently during working because of the structure failure of hoist boom,which result in severe economic loss and casualties. So,the method combining probabilistic and non-probabilistic hybrid reliability theory with Bayesian Network is put forward to analyze the reliability of hoist boom structure. Probabilistic and nonprobabilistic hybrid model is built aiming at the interval variables and random variables to calculate the failure probability of boom buckling under different conditions. Bayesian Network model is applied to calculate the importance index of different failure cause. Finally,the validity of the method is verified according to the instance analysis,which can provide evidence for hoist boom design based on reliability.